Jasa Promosi Video agar FYP di Aplikasi Tiktok dalam Kajian Hukum Ekonomi Syariah - M Kemas Setiawan; Yuswalina Yuswalina; Dodi Irawan (Journal of Sharia and Legal Science, 2026)
Social media is a digital platform that allows users to interact, share information, and engage in various activities, including digital-based economic activities. One rapidly growing platform is TikTok, which serves not only as an entertainment medium but also as a means of promotion and marketing through its For You Page (FYP) feature. This study aims to analyze the video promotion service system on the TikTok application and review this practice from the perspective of Islamic economic law. The research method used is a normative juridical approach with a qualitative approach, namely through a literature study of various legal sources and relevant literature. The results show that video promotion services on TikTok are a form of service aimed at increasing the reach and visibility of content through the platform's algorithmic mechanism. This practice involves a contractual relationship between the service provider and the service user who conduct transactions based on a specific agreement. From the perspective of Islamic economic law, the practice of video promotion services to achieve FYP can be categorized as an ijarah contract, namely an agreement to utilize services for a certain fee. As long as it meets the pillars and requirements of the contract, such as the existence of an agreement, clarity of the service object, and does not contain prohibited elements, this practice is considered compliant with Islamic principles. This research contributes to understanding how digital economic practices, particularly in social media, can be analyzed and integrated within the framework of Islamic economic law.